Identification of critical factors affecting energy consumption in the blast furnace production process - Zaselskyi , V.Y.; Popolov , D.V. (Theory and Practice of Metallurgy, 2024)
The purpose of the research is to identify factors that affect the energy intensity of blast furnace production, determination and provision of scientifically based recommendations on the use of the necessary equipment, which allows to reduce energy consumption in the existing technological paths. The identification of factors was identified by expert evaluation. At the first stage an expert group of specialists from the above-mentioned production was formed, at the second stage was to determine their competence; the third stage the Delphi method was used, and the experts identified the factors that affect the energy intensity of blast furnace production; at the fourth stage, the assessed the degree of influence of changes in the selected factors. The data obtained were processed statistically and ranked in descending order of influence on the energy intensity of the studied production. The degree of consistency of experts' opinions was assessed using the concordance coefficient. According to the results of the expert assessment, it was found that the greatest impact on the energy intensity of blast furnace production is made by the content of substandard fractions of coke and the iron-containing part of the charge. Therefore, attention was paid to preparatory processes related to the separation of the metallurgical charge by size and the analysis of the formation of the particle size distribution of charge materials at different parts of the route of its processing and transportation to the blast furnace. The analysis of the data showed that in the charge preparation path there is a constant increase in the content of substandard material in the volume of the charge, while the screening efficiency of raw materials does not exceed 50 % for sinter and 60 % for coke, which does not allow to meet the necessary technological requirements for acceptable percentages of fines. It was found out that the initial part of the charge contains up 8.6 % and 19.9 % of clogging particles, the size of which is close to the size of the sieve aperture (5 mm for agglomerate and 25 mm for coke), and therefore, the probability of their passage through the holes of the screening surface are close to zero. When screening the materials under study materials in a thick layer, hard-to-pass particles through the holes of the sieving clog the screening surface over time, resulting in a decrease in screening efficiency of the substandard part of the metallurgical charge, which significantly affects energy intensity of blast furnace production. It is recommended to find modern technical solutions that would allow to increase the efficiency of screening, taking into account the reduction of clogging of the screening surface, and at the same time to solve the issue of quality stabilization of the particle size distribution of the charge fed into the blast furnace.